Կրկնավոր բարդությունների ձայնդարձով և հերթագայությամբ տիպերն Աստվածաշունչ Մատյանում - Խաչատրյան, Լ. (ՀՀ ԳԱԱ հրատ.)
The analysis of the word stock of the Armenian translation of the Bible shows that among the word-formation types used here the alternation type of reduplication, forms a unique group, which is characterized by the following formation factors: 1) alternation in the first component e.g բարբառ, թօթափել, կսկծելի etc.; 2) alternation in the second component. Изучение словарного состава армянского перевода Библии показывает, что среди использованных словообразовательных типов особое место занимает тип редупликации с чередованием звуков, характеризующийся следующими формообразующими факторами: 1) чередование в первом компоненте слов: բարբառ, թօթափել, կսկծելի и т.д.; 2) чередование во втором компоненте.
Keywords: Աստվածաշունչ